2010
DOI: 10.1007/s10388-010-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic enucleation for small-sized gastrointestinal stromal tumor of the esophagus: report of two cases

Abstract: Gastrointestinal stromal tumors (GISTs) rarely occur in the esophagus. Surgical approaches for such tumors have not been established, since the standard wedge or segmental resection that is used for intra-abdominal GIST is not possible in the esophagus. We report two cases of small esophageal GIST in which thoracoscopic enucleation was performed. Both patients underwent the thoracoscopic surgery using four trocars. The tumor size was 43 and 32 mm in patients 1 and 2, respectively. The operating time was 240 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…An open thoracotomy is the conventional approach for removing an esophageal cyst. On the other hand, a thoracoscopic approach, including VATS, has more advantages for improving the postoperative course when compared with open thoracic surgery, since a thoracoscopic approach can eliminate postoperative respiratory and wound-related complications [8][9][10][11]. A literature search of the PubMed database was performed using esophagus, bronchogenic cyst, and thoracoscopic surgery as keywords and a publication range of between 1980 and 2010.…”
Section: Discussionmentioning
confidence: 99%
“…An open thoracotomy is the conventional approach for removing an esophageal cyst. On the other hand, a thoracoscopic approach, including VATS, has more advantages for improving the postoperative course when compared with open thoracic surgery, since a thoracoscopic approach can eliminate postoperative respiratory and wound-related complications [8][9][10][11]. A literature search of the PubMed database was performed using esophagus, bronchogenic cyst, and thoracoscopic surgery as keywords and a publication range of between 1980 and 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, thoracoscopic esophagectomy and enucleation have been successfully performed for esophageal GISTs (13,25,45). As minimally invasive esophagectomy has been performed widely for esophageal cancer, this technique can be applied for esophageal GISTs.…”
Section: Surgical Therapy For Esophageal Gistsmentioning
confidence: 99%
“…Over the last two decades, thoracoscopic surgery has attracted much attention as a less invasive approach for the treatment for benign and malignant diseases [13][14][15]. In 1992, Cuschieri et al [16] first reported performing thoracoscopic minimally invasive esophagectomy (MIE) for esophageal cancer, which sparked the interest of many surgeons because MIE has the potential to lower the morbidity associated with resection and to enable a quicker return to normal function.…”
Section: Introductionmentioning
confidence: 99%